2017
DOI: 10.1101/212910
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Noninvasive Molecular Clock for Fetal Development Predicts Gestational Age and Preterm Delivery

Abstract: We performed a high time-resolution, longitudinal study of normal pregnancy development by measuring cell-free RNA (cfRNA) in blood from women during each week of pregnancy. Analysis of tissue-specific transcripts in these samples enabled us to follow fetal and placental development with high resolution and sensitivity, and also to detect gene-specific responses of the maternal immune system to pregnancy. We established a "clock" for normal pregnancy development and enabled a direct molecular approach to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Our study provides insight into potential immune mechanisms that could drive preterm birth, but did not identify a clear biomarker for preterm birth akin to the signature recently identified using analysis of cell-free DNA (31). In fact, it will be important to validate such signatures in cohorts drawn from a range of geographic areas, with a particular focus on Africa and Asia where preterm birth is most prevalent.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our study provides insight into potential immune mechanisms that could drive preterm birth, but did not identify a clear biomarker for preterm birth akin to the signature recently identified using analysis of cell-free DNA (31). In fact, it will be important to validate such signatures in cohorts drawn from a range of geographic areas, with a particular focus on Africa and Asia where preterm birth is most prevalent.…”
Section: Discussionmentioning
confidence: 79%
“…Consistent with the idea that preterm birth is an inflammatory state, monocytes from women with a history of preterm birth demonstrated enhanced inflammatory responses in response to stimulation in vitro (30). More recently, significant progress was made in identifying signatures predictive of preterm birth and delivery timing using cell-free RNA in the blood (31,32). The studies performed to date have varied in the specific gene signatures identified, and in fact, there has been very poor agreement between studies in the genes identified (33).…”
mentioning
confidence: 87%
“…eQTL results from the GTEx and GEUVADIS data bases for skin tissue and lymphoblastoid cell lines, respectively, support this suggestion. However, to fully investigate this hypothesis, larger sample sizes and further functional follow-up experiments are needed, including fine-mapping of the locus and characterization of pro-inflammatory cytokine signalling shortly before parturition e.g., through non-invasive techniques allowing quantification of cell-free fetal RNA 39,40 and measurement of cytokine levels.…”
Section: Discussionmentioning
confidence: 99%